(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
As a result of data processing on benzene adsorption on a surface of silica with graft superficial fragments oligostyrene it was found , that for characterization of textural parametres of sorbents, the possibility of the isotherm equation of adsorption BET (Brunauer, Emmett, Teller) is strongly limited. It was shown, that for more reliable definition of structural characteristics of sorbents with graft superficial connections expediently instead of using twoparametrical isotherm equation BET to apply Guggengeime, Anderssen and de Boer three-parametrical equation.